Observations and modeling of shear stress reduction and sediment flux within sparse dune grass canopies on managed coastal dunes. Issue 5 (22nd January 2023) - Dickey, John; Wengrove, Meagan; Cohn, Nicholas; Ruggiero, Peter; Hacker, Sally D.
Abstract: Wind flow over coastal foredunes adapts to vegetation, resulting in spatial gradients in bed shear stresses that contribute to the formation of localized bedforms. Understanding, and having the capability to numerically predict, the distribution of sediment deposited within sparsely vegetated dune complexes is critical for quantifying the ecological, protective, and economic benefits of dune management activities. Data from wind tunnel experiments have indicated that there is a spatial lag from the canopy leading edge to a downwind location where sediment deposition first occurs. The length scale of this deposition lag is further quantified here using new field measurements of aeolian sediment transport across sparsely vegetated managed dune systems in Oregon, USA. We develop a deposition lag length scale parameter using both lab and this new field data and then incorporate this parameter into the process‐based aeolian sediment transport model, Aeolis, which also includes a new far‐field shear stress coupler. Results from numerical simulations suggest that the spatial deposition lag effect is significant for model skill in sparsely vegetated dunes. We observe with field and laboratory observations that, as canopy density increases, the length of the deposition lag decreases. As such, within the model framework the implementation of the deposition lag length does not affect the results of models of coastal dune geomorphological evolution within higher density canopies. Dune canopy density can vary due to natural (e.g., storm overwash, burial, die‐off) or anthropogenic (e.g., managed plantings, dune grading) processes. Abstract : The far‐field (>1 m) effects of dune grass and spatial deposition patterns are investigated in sparsely vegetated dune grass canopies. Field observations and process‐based numerical models of aeolian processes are utilized to propose a new length scale parameter (L D ) to account for spatial lags in deposition that are dependent on the vegetation cover and canopy height (L c ).